2021
DOI: 10.3390/ani11082396
|View full text |Cite
|
Sign up to set email alerts
|

Circular PPP1R13B RNA Promotes Chicken Skeletal Muscle Satellite Cell Proliferation and Differentiation via Targeting miR-9-5p

Abstract: Skeletal muscle plays important roles in animal locomotion, metabolism, and meat production in farm animals. Current studies showed that non-coding RNAs, especially the circular RNA (circRNA) play an indispensable role in skeletal muscle development. Our previous study revealed that several differentially expressed circRNAs among fast muscle growing broilers (FMGB) and slow muscle growing layers (SMGL) may regulate muscle development in the chicken. In this study, a novel differentially expressed circPPP1R13B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…For example, the expression of MyHC , MyoG and MEF2C promoted the differentiation of goat SMSCs, while TGFβ1 inhibited the differentiation of the cells [ 27 , 47 , 48 ]. Meanwhile, MyHC is a myogenesis marker protein, in that the area of MyHC-labeled myotubes is proportional to the degree of differentiation of SMSCs and the formation of myotubes [ 13 , 27 ]. These results suggest that circ_003628 promotes the differentiation of goat SMSCs, and further conclude that the circRNA may also increase caprine skeletal muscle mass by promoting differentiation of goat SMSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the expression of MyHC , MyoG and MEF2C promoted the differentiation of goat SMSCs, while TGFβ1 inhibited the differentiation of the cells [ 27 , 47 , 48 ]. Meanwhile, MyHC is a myogenesis marker protein, in that the area of MyHC-labeled myotubes is proportional to the degree of differentiation of SMSCs and the formation of myotubes [ 13 , 27 ]. These results suggest that circ_003628 promotes the differentiation of goat SMSCs, and further conclude that the circRNA may also increase caprine skeletal muscle mass by promoting differentiation of goat SMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of RNA-Seq and bioinformatics technologies, thousands of unique circRNAs have been annotated in skeletal muscle tissues in chickens [ 13 ], cattle [ 14 ], goats [ 15 ], pigs [ 16 ], and sheep [ 17 ]. For example, Lei et al [ 18 ] identified 5755 differentially expressed circRNAs in breast muscle tissue of Shouguang chickens between embryonic periods and postnatal periods.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth emphasizing that the connection between Focal adhesion and ECM regulates several intracellular pathways of cell motility, proliferation, and differentiation (57). The PI3K-Akt signaling pathway has also been shown to increase skeletal muscle cell proliferation and differentiation (58,59). We hypothesize that these differentially expressed genes enriched in these three signal pathways are engaged in skeletal muscle differentiation functions, resulting in differential expression.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we predicted the potential target miRNAs using RNAhybrid software, 23 miRNAs were found may be regulated by circITSN2 (Supplementary Table 4). Previous reports showed that circRNAs and miRNAs in ceRNA regulatory network have opposite expression patterns (Ouyang et al, 2018a;Shen et al, 2021b), and circITSN2 gradually increased during embryonic muscle development. Besides, previously we sequenced the miRNAs of the breast muscle of embryonic chicks at E10, E13, E16, and E19 (SRA database with accession number PRJNA516545).…”
Section: Circitsn2 Acts As a Mirna Sponge Of Mir-218-5pmentioning
confidence: 94%